Association between serum uric acid and bone mineral density in patients with type 2 diabetes: A 6-year longitudinal study in China. Issue 17 (30th April 2021) - Yang, Kun; Miao, Huilei; Zhao, Ruijie; Wu, Xiling; Liu, Bo; Zheng, Shuiqiao; Huang, Dan; Ping, Zhao
Abstract : Abstract: The relationship between serum uric acid (UA) and bone mineral density (BMD) has been proposed by several researchers. However, there has been no consensus regarding the relationships among serum UA, diabetes, and BMD. The aim of this study is to investigate the association between UA, BMD, and at least osteopenia in type 2 diabetes patients. This research was a longitudinal study performed at Xiao-Tang-Shan Hospital in Beijing. Type 2 diabetes diagnosis was consistent with the WHO standard classification. Participants with osteopenia or osteoporosis documented by dual-energy X-ray absorptiometry were defined as having "at least osteopenia." A generalized additive model and multivariable logistic regressions were performed to explore the relationship between serum UA and at least osteopenia. Receiver operating characteristic analysis was conducted. Propensity score matching was used to verify the correctness of the cutoff point. In total, 3476 type 2 diabetes patients free of any osteopenia-related diseases were recruited in 2012 and followed up to 2018. The general proportions of patients with at least osteopenia in 2018 was 16.46% (572/3476). Serum UA was negatively associated with BMD stratified by sex, age group, and BMI level. Setting the first quartile as the reference, the risk of at least osteopenia in the fourth quartile was significant among all patients (odds ratio [OR]: 0.75; 95% confidence interval [CI]: 0.57, 0.98) and specifically in females (OR: 0.79; 95% CI: 0.43, 0.97), patients aged over 50 years (OR: 0.79; 95% CI: 0.60, 0.97) and patients with a BMI greater than 25 (OR: 0.74; 95% CI: 0.47, 0.97). The optimal cutoff point for the serum UA level to distinguish at least osteopenia in diabetic patients was 395 μmol/L. Serum UA concentration is negatively associated with the occurrence of at least osteopenia in Chinese patients with type 2 diabetes. Abstract : Supplemental Digital Content is available in the text